Role and perspective of sport science in health promotion and elite sport - Kim, K. (The Asian Journal of Kinesiology, 2019)
OBJECTIVES The study aimed to investigate the role and perspective of sport science in health promotion and the improvement of elite sport performance. METHODS The study was performed by the review of previous papers and manuscripts related to sport science development and future. RESULTS Sport science has emerged as an important part of human science since long ago. In the BC 1800s,evidence of sports being used as treatment for diseases was the foundation for `Exercise Medicine` , as suggested by ACSM in 2007. Similar to the characteristics of other academics, sport science also shows a periodic wave, alternating between a flow of segmentation and specialization and a flow of convergence and interdependence. The sport science approach not only prevents diseases but also aids in the treatment of diseases. The process of development of evidence-based sports science includes questions on the applicability on the actual setting and collecting evidences of its answer. Sport science must be recognized as an important academic field that provides clear answers to the questions posed by the public, athletes, and coaches. Convergence with diverse modern sciences and evolution is suggested. Convergence of culture industry and increased participation in sports have brought positive effects, including healthy lifestyles, ICT innovation, IT software utilization, sociability among the elderly, development of global sport networks, strengthened tourism industry, and development of sensory virtual reality. CONCLUSIONS Relative to other academic fields, sport science requires more reality and productivity. Active attempts to investigate in both laboratories and fields, analysis of actual settings, and experience-based interpretation are crucial to truly improve performance and further develop sport science. Sport science in the future will require association and harmony with more diverse academic fields, as well as utilization of modern technology and communication among diversified information technologies. An active association between sport science and sport culture is emphasized.